2023
DOI: 10.1002/etc.5641
|View full text |Cite
|
Sign up to set email alerts
|

The Concentrations, Sources, Ecological, and Human Health Risk Assessment of Heavy Metals in Roadside Soils of Six Cities in Shanxi Province, China

Abstract: Roadside soils are regarded as a reservoir for heavy metal pollution, which potentially leads to ecosystem deterioration as well as serious hazard to human health. A comprehensive investigation was conducted for the levels, relationship with soil properties, and potential sources of heavy metals (Hg, Cu, Zn, Pb, Cd, and Cr) in roadside soils in six cities (Changzhi, Jincheng, Yuncheng, Linfen, Xinzhou, Datong) of Shanxi Province; and the corresponding ecological risk and human health risk associated with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Wu [24] found that Cd, Pb, and As pollution is severe in sewage-irrigated farmland along Dongdagou Creek in Baiyin City. Ma [40] found that sewage irrigation related to industrialization is the main source of potentially toxic elements in the soil. The farmland in Dongdagou is a "sewage irrigation area" [41].…”
Section: Analysis Of Potentially Toxic Element Sources In Soilmentioning
confidence: 99%
“…Wu [24] found that Cd, Pb, and As pollution is severe in sewage-irrigated farmland along Dongdagou Creek in Baiyin City. Ma [40] found that sewage irrigation related to industrialization is the main source of potentially toxic elements in the soil. The farmland in Dongdagou is a "sewage irrigation area" [41].…”
Section: Analysis Of Potentially Toxic Element Sources In Soilmentioning
confidence: 99%
“…Different regions universally face varying degrees of heavy metal pollution, primarily caused by the release of heavy metal waste during industrial, mining, and agricultural processes. These pollutants enter the soil through processes such as atmospheric deposition and water leakage, causing the accumulation of heavy metals in the soil to exceed safety standards [ 5 , 6 , 7 ]. Heavy metal pollution has severe implications for the environment and human health.…”
Section: Introductionmentioning
confidence: 99%